Multicultural Education in Social Studies Textbooks in South Korea and the United States: A Comparative Analysis - Kim, Younghan (My University, 2013)
Today, globalization has increased cross-border migration in many countries. The public school classroom in the United States has been getting more diverse, linguistically, culturally, racially, and ethnically. Classrooms in South Korea are also becoming linguistically, culturally, racially, and ethnically diverse because of the fast growth of immigration since the 1990s. In nation-states, implementing theories, practices, ideals, values of multicultural education in curricula is a responsibility for the wellbeing and academic success of all children. This dissertation examined how social studies textbooks in South Korea and the United States implement suggestions that multicultural education scholars recommend for cultural pluralism, educational equality, and social justice to reduce gaps between theories and practices. Five social studies textbooks were analyzed. Since the Seattle (WA) Public Schools recently adopted only one textbook for use in 2012-2013 in regular U.S. history classes, History Alive! Pursuing American Ideals was analyzed. Two Korea History and two Society and Culture texts randomly selected from the approved list by the South Korean Ministry of Education were analyzed as the combination of the two subjects is more equivalent to U.S. history. This study found the selected textbooks did an inadequate job of adopting multicultural education theories suggested by scholars although there are minor differences among the three sets of textbooks. Although there are not many, few stereotypical images are still found in all three sets of textbooks. Textbooks are dominated by stories of mainstreamers in each country. The coverage of ethnic minorities is often limited to roles and topics related to racial issues such as discrimination. There are no stories of how different minority groups interact with each other, and there is practically no contemporary coverage of social actions by ethnic minorities for social justice.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: Multicultural education; education - seattle